2022
DOI: 10.1088/1742-6596/2150/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of oil by SiO2-nanofluid from a microporous medium: microfluidic experiments

Abstract: In this work, the process of displacing oil from a microfluidic chip that simulates a porous medium is studied. Experimental photographs of the process of oil displacement by water and SiO2-nanofluid are presented. It is shown that the use of nanofluid increases the oil displacement efficiency by 16%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…In the challenging high-salt and low-permeability reservoir conditions, this nano-SiO 2 material was more effective than water flooding, leading to a significant 14.6% increase in oil recovery. Pryazhnikov et al 36 conducted microfluidic experiments to model the oil displacement process of nano-SiO 2 in porous media. They found that changing the wettability could increase the oil recovery rate by 16%.…”
Section: Introductionmentioning
confidence: 99%
“…In the challenging high-salt and low-permeability reservoir conditions, this nano-SiO 2 material was more effective than water flooding, leading to a significant 14.6% increase in oil recovery. Pryazhnikov et al 36 conducted microfluidic experiments to model the oil displacement process of nano-SiO 2 in porous media. They found that changing the wettability could increase the oil recovery rate by 16%.…”
Section: Introductionmentioning
confidence: 99%